ESL undergraduates' patterns of plagiarism in academic essays based on print or Internet sources - Zangenehmadar, Samaneh; Tan, Bee Hoon (Universiti Putra Malaysia Press, 2017)
One of the most important issues among ESL students is inappropriate use of source material in their academic writing. As a result, plagiarism is more common among ESL students. The purpose of this study is to investigate the effects of source information type (print versus online) on plagiarism patterns in students' academic essays. The data of this study comprised Malaysian undergraduates' essays written based on references to print or Internet sources. The originality reports of the students' essays submitted to Turnitin were then checked against the original sources to code various instances of similarity. The results indicated that direct copying with no reference and quotation marks was the most frequent plagiarism pattern in students' essays. Moreover, the study found a statistically significant difference between plagiarism patterns in students' writing based on print and online source modes.